Sliding mode voltage control of boost converters in DC microgrids. (April 2018) - Cucuzzella, Michele; Lazzari, Riccardo; Trip, Sebastian; Rosti, Simone; Sandroni, Carlo; Ferrara, Antonella
Abstract: This paper deals with the design of a robust decentralized control scheme for voltage regulation in boost-based DC microgrids. The proposed solution consists of the design of a suitable manifold on which voltage regulation is achieved even in presence of unknown load demand and modeling uncertainties. A second order sliding mode control is used to constrain the state of the microgrid to this manifold by generating continuous control inputs that can be used as duty cycles of the power converters. The proposed control scheme has been theoretically analyzed and validated through experiments on a real DC microgrid. Highlights: A robust voltage control scheme for boost converters in DC microgrids is proposed. The control scheme is scalable and fully decentralized. Second order sliding mode with PWM implementation fixes the switching frequency. The stability analysis provides tuning rules. Experiments validate the proposed strategy and confirm the theoretical results.